MODELAGEM PARA O SOFTWARE VIRTUAL-TANEB BASEADO NA TEORIA DA RESPOSTA AO ITEM PARA AVALIAR O RENDIMENTO DOS ALUNOS - Veras, Jaclason Machado (2010)
This work proposes a general modeling for an educational software which will serve to verify the knowledge of geometry of fourth grade students of elementary school. The Virtual-Taneb will be based on Basic Education Evaluation System (SAEB) which is an evaluative instrument used in Brazil originated from the guidelines of the National Assessment of Educational Progress (NAEP), which is currently applied manually by written tests. One of the motivations for developing this tool was to reduce the delivery time of obtained results through the resolution of written tests, obeying Basic Education Courseworks. Another motivation was the inclusion of the Item Response Theory (IRT) as an educational evaluation quantifier and qualifier, allowing a statistical analysis from items such as central elements of tests, since the need to monitor the development process of educational evaluation systems. However, there are factors that suppress the use of IRT on a large scale, such as customizing each application and the mathematical complexity of the methods involved. This prototype of educational software will be applied to elementary schools in the State of Maranhão, Brazil. It will be adapted to the cognitive level of students through the inclusion of recourses from the area of Artificial Intelligence and besides it will enable an effective analysis of students knowledge using the IRT on the responses made. Virtual-Taneb will provide some benefits to the Brazilian society, as to favor a long-term reduction of economic investment in the evaluation process, resulting in improvements for present and future generations. Another benefit is the adequation possibility of this software to other evaluation systems, as an example, the International Program of Students Assessment (PISA), the National Examination of High School (ENEM), Prova Brasil, among others. In the future, though the adaptation of the Virtual-Taneb software, there will be the possibility of adding other subjects to the test.